Lithium ion battery graphite negative electrode material and preparation method thereof
By adjusting the particle size distribution and adopting specific granulation equipment in the artificial graphitization secondary particle process, the performance problems of negative electrode materials caused by incomplete removal of fine powder in the existing process are solved, and high tap density, low specific surface area and high The capacity of negative electrode material improves the performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202310775610.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-27
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-06-27
AI Technical Summary
In the existing artificial graphitization secondary particle process, the fine powder content after raw material crushing and grading is not clean enough, resulting in the low tap density of the negative electrode material after graphitization, large specific surface area and low capacity, which affects the compatibility of the battery. Rate performance and cycle performance.
By reducing the particle size span range, improving the particle size, removing some fine powder with small particle size, controlling the DV10 of the material after grading treatment to 4.0-4.5μm or 4.5-5.0μm, and using a specific horizontal or vertical kettle to construct a specific horizontal or vertical kettle. The granulation equipment is carried out in a granulation process, and the particle size setting after grading is set to improve the performance of the negative electrode material after graphitization.
The graphitized negative electrode material has high tap density, low specific surface area, high capacity, and good compatibility with the electrolyte, excellent circulation performance, and good battery coating processing performance.
Smart Images

Figure CN116902973B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of graphite material preparation, and in particular to a lithium ion battery graphite negative electrode material and a preparation method thereof. Background Art
[0002] At present, the negative electrode materials of new energy lithium-ion batteries are mainly natural graphite and artificial graphite; the negative electrode material is an important component of lithium-ion batteries, and its performance affects the key indicators of lithium-ion batteries such as safety, specific capacity, rate performance, cycle life, high and low temperature performance, etc. Artificial graphite has good compatibility with electrolytes, good cycle performance and rate performance, and is the preferred negative electrode material for lithium-ion batteries. At present, the secondary particle processes of artificial graphitization include coarse crushing, pulverization, grading, coating, shaping, pre-carbonization, and graphitization. This process has the following shortcomings: due to the insufficient removal of fine powder content after raw material pulverization and grading, the coating process will cause the aggregate to bond with the fine powder, resulting in low tap density after graphitization, large specific surface area, and low capacity. After being made into lithium-ion batteries, there are problems with poor compatibility with electrolytes, rate performance, and cycle performance.
[0003] Therefore, it is necessary to provide a lithium ion battery graphite negative electrode material with high tap density and a preparation method thereof to solve the current defects. Summary of the invention
[0004] In view of the fact that the fine powder content is not removed cleanly after raw material crushing and classification in the prior art, the aggregate and fine powder are bonded together in the coating process, resulting in the negative electrode material after graphitization having problems such as low tap density, large specific surface area, and low capacity. The purpose of the present invention is to provide a lithium ion battery graphite negative electrode material with high tap density, small specific surface area, and high capacity. The graphite negative electrode material has the characteristics of good compatibility with electrolyte, excellent cycle performance, and good battery coating processing performance.
[0005] To achieve the above object, the present invention provides a method for preparing a graphite negative electrode material for a lithium ion battery, comprising the steps of:
[0006] (1) roughly crushing the raw materials to obtain material A;
[0007] (2) crushing material A to obtain material C;
[0008] (3) subjecting material C to classification treatment to obtain material D, wherein the DV50 of material D is 11-12 μm, and the DV10 is 4.0-4.5 μm or 4.5-5.0 μm;
[0009] (4) Mixing material D and an adhesive to obtain material E;
[0010] (5) granulating material E to obtain material F, wherein the granulation equipment is a horizontal kettle or a vertical kettle;
[0011] (6) Shaping material F to obtain material G;
[0012] (7) Pre-carbonizing material G to obtain material H;
[0013] (8) Graphitizing material H to obtain a graphitized material.
[0014] In the prior art, the particle size range generally used in the classification stage has a large span and contains fine powder, such as 3.5-4.5μm, which will lead to insufficient removal of fine powder content in the subsequent process, and the aggregate and fine powder in the coating process will be bonded together, resulting in the negative electrode material after graphitization having problems such as low tap density, large specific surface area, and low capacity. The inventor found through many experiments during the work process that by reducing the particle size span range, appropriately increasing the particle size, removing some small-size fine powder, and controlling the DV10 of the material in this step to 4.0-4.5μm or 4.5-5.0μm through classification treatment, the capacity after graphitization can be increased and the specific surface area after graphitization can be reduced. At the same time, the inventors also found that in this process, the continuous kettle coating granulation process cannot achieve relatively good specific surface area, tap density, compaction, gram capacity, oil absorption value and other properties. When a specific horizontal kettle or vertical kettle granulation equipment is selected for the granulation process, combined with the particle size setting after classification of the present invention, the product particles can show that the secondary particles contain a small amount of single particles, making the particle size distribution more reasonable, thereby improving the tap density, compaction density, reducing expansion, and improving the cycle performance. The obtained negative electrode material has the characteristics of high capacity, high compaction, good compatibility with the electrolyte, excellent cycle performance, and good battery coating processing performance.
[0015] In some embodiments, the raw material is selected from at least one of petroleum coke, coal-based coke, needle coke, and semi-coke. By way of example, the raw material is petroleum coke green coke, but is not limited thereto.
[0016] In some embodiments, the DV50 of material C is 10-11 μm, and the DV10 is 2.8-3.5 μm, but not limited thereto.
[0017] In some embodiments, the adhesive is selected from at least one of high temperature asphalt, resin, and liquid asphalt, but is not limited thereto.
[0018] In some embodiments, the equipment for batch mixing is a horizontal ribbon batch mixer or a VC3000 batch mixer.
[0019] In some embodiments, the batch mixing equipment is a horizontal screw ribbon batch mixing machine, and the temperature rise curve of the horizontal screw ribbon batch mixing machine is controlled to rise from room temperature to 300°C within 1 hour, then rise to 650°C within 3 hours, and keep warm for 3 hours, and the N2 flow rate is 0.5-1.0m 3 / h.
[0020] In some embodiments, the pre-carbonization temperature is 800-1200°C.
[0021] In some embodiments, the pre-carbonization equipment is selected from a low-temperature carbonization furnace and a shuttle furnace.
[0022] In some embodiments, the temperature of graphitization is 2900-3200°C.
[0023] In some embodiments, the graphitization equipment is selected from one of an Acheson furnace, a box furnace, and an inner series furnace.
[0024] Correspondingly, the present invention also provides a lithium ion battery graphite negative electrode material, which is prepared by the above preparation method. The prepared lithium ion battery graphite negative electrode material has the characteristics of high capacity, high compaction, good compatibility with electrolyte, excellent cycle performance, and good battery coating processing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM image of the graphite negative electrode material for a lithium-ion battery according to Example 2 of the present invention.
[0026] Figure 2 The capacity retention curves of the batteries made of the negative electrode materials of the embodiments and comparative examples after 500 cycles are shown. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0028] Example 1
[0029] A lithium-ion battery graphite negative electrode material comprises the following steps:
[0030] (1) The raw material petroleum coke is roughly crushed by a jaw crusher to obtain material A1 with a particle size of 0-5 mm;
[0031] (2) Material A1 was crushed by a crusher (260 mechanical mill) to obtain material C1 with a particle size DV50 of 10-11 μm and DV10 of 2.8-3.5 μm;
[0032] (3) The material C1 is subjected to classification treatment by an air flow classifier to obtain a material D1 having a DV50 of 11-12 μm and a DV10 of 4.0-4.5 μm;
[0033] (4) Material D1 and adhesive high-temperature asphalt are mixed in a horizontal ribbon mixer at a time of 120 min / kettle, 2 T / kettle, and a rotation speed of 28 r / min to obtain material E1;
[0034] (5) Material E1 was granulated through a horizontal reactor of a coating device. The temperature was raised from room temperature to 300°C within 1 hour, then to 650°C within 3 hours, and kept at this temperature for 3 hours. The N2 flow rate was 0.5-1.0 m 3 / h, and obtain material F1;
[0035] (6) Material F1 is shaped by a shaping machine 80 to achieve full collection of the material and obtain material G1;
[0036] (7) Pre-carbonizing material G1 in a low-temperature carbonization furnace to obtain material H1;
[0037] (8) The material H1 is graphitized by an Acheson furnace to obtain a graphitized material, i.e., a graphite negative electrode material.
[0038] Example 2
[0039] A lithium-ion battery graphite negative electrode material comprises the following steps:
[0040] (1) The raw material petroleum coke is roughly crushed by a jaw crusher to obtain material A2 with a particle size of 0-5 mm;
[0041] (2) Material A2 was crushed by a crusher (260 mechanical mill) to obtain material C2 with a particle size DV50 of 10-11 μm and DV10 of 2.8-3.5 μm;
[0042] (3) The material C2 is subjected to classification treatment by an air flow classifier to obtain a material D2 having a DV50 of 11-12 μm and a DV10 of 4.5-5.0 μm;
[0043] (4) Material D2 and adhesive high-temperature asphalt are mixed in a horizontal ribbon mixer at a time of 120 min / kettle, 2 T / kettle, and a rotation speed of 28 r / min to obtain material E2;
[0044] (5) Material E2 is granulated through a coating equipment vertical reactor. The temperature rise curve is from room temperature to 300°C within 1 hour, then to 650°C within 3 hours, and kept at this temperature for 3 hours. The N2 flow rate is 0.5-1.0m 3 / h, and obtain material F2;
[0045] (6) Material F2 is shaped by a shaping machine 80 to achieve full collection of the material and obtain material G2;
[0046] (7) Pre-carbonizing material G2 in a low-temperature carbonization furnace to obtain material H2;
[0047] (8) The material H2 is graphitized by an Acheson furnace to obtain a graphitized material, i.e., a graphite negative electrode material.
[0048] Comparative Example 1
[0049] A lithium-ion battery graphite negative electrode material comprises the following steps:
[0050] (1) The raw material petroleum coke is roughly crushed by a jaw crusher to obtain material A3 with a particle size of 0-5 mm;
[0051] (2) Material A3 was crushed by a crusher (260 mechanical mill) to obtain material C3 with a particle size DV50 of 10-11 μm and DV10 of 2.8-3.5 μm;
[0052] (3) The material C3 is classified by an air flow classifier to obtain a material D3 having a DV50 of 11-12 μm and a DV10 of 4.5-5.0 μm;
[0053] (4) Material D3 and adhesive high-temperature asphalt are mixed in a horizontal ribbon mixer at a time of 120 min / kettle, 2 T / kettle, and a rotation speed of 28 r / min to obtain material E3;
[0054] (5) Material E3 was granulated by continuous granulation in the coating equipment. The temperature rise curve was from room temperature to 300°C within 1 hour, then to 650°C within 3 hours, and kept at this temperature for 3 hours. The N2 flow rate was 0.5-1.0m 3 / h, and obtain material F3;
[0055] (6) Material F3 is shaped by a shaping machine 80 to achieve full collection of the material and obtain material G3;
[0056] (7) Pre-carbonizing material G3 in a low-temperature carbonization furnace to obtain material H3;
[0057] (8) The material H3 is graphitized in an Acheson furnace to obtain a graphitized material, i.e., a graphite negative electrode material.
[0058] Comparative Example 2
[0059] A lithium-ion battery graphite negative electrode material comprises the following steps:
[0060] (1) The raw material petroleum coke is roughly crushed by a jaw crusher to obtain material A4 with a particle size of 0-5 mm;
[0061] (2) Material A4 was crushed by a crusher (260 mechanical mill) to obtain material C4 with a particle size DV50 of 10-11 μm and DV10 of 2.8-3.5 μm;
[0062] (3) The material C4 is subjected to classification treatment by an air flow classifier to obtain a material D4 having a DV50 of 11-12 μm and a DV10 of 3.5-4.5 μm;
[0063] (4) Material D4 and adhesive high-temperature asphalt are mixed in a horizontal ribbon mixer at a time of 120 min / kettle, 2 T / kettle, and a rotation speed of 28 r / min to obtain material E4;
[0064] (5) Material E4 was granulated in a vertical reactor of the coating equipment. The temperature was raised from room temperature to 300°C within 1 hour, then to 650°C within 3 hours, and kept at this temperature for 3 hours. The N2 flow rate was 0.5-1.0 m 3 / h, and obtain material F4;
[0065] (6) Material F4 is shaped by a 80 shaping machine, with a material yield of 95%, to obtain material G4;
[0066] (7) Pre-carbonizing material G4 in a low-temperature carbonization furnace to obtain material H4;
[0067] (8) The material H4 is graphitized in an Acheson furnace to obtain a graphitized material, i.e., a graphite negative electrode material.
[0068] Figure 1 The SEM image of the graphite negative electrode material of Example 2 is shown. It can be seen from the figure that the particle structure shows that secondary particles contain a small number of single particles. Under the same volume space, the wider the particle size distribution, the smaller particles will fill the gaps between large particles, thereby increasing the tap density accordingly. Because the slurry with high tap density has low viscosity and high solid content, the coating process is easier.
[0069] The graphite negative electrode materials prepared in the embodiments and comparative examples were tested for particle size DV50 (test equipment: Mastersizer 3000, test standard: GB / T 19077-2016), specific surface area (test equipment: Tristar II 3020, test standard: GB / T 24533-2009), tap density 20 KN (BT-302, GB / T 5162-2006), compaction density (test equipment: Sansi Zongheng UTM 7305, test standard: GB / T 24533-2019), oil absorption value (test equipment: S-500 oil absorption tester, test standard: GB / T 3780.2-2007), and gram capacity (test equipment: Blue Electric Button Test System, test standard: GB / T 24533-2009), and the results are shown in Table 1.
[0070] The graphite negative electrode material prepared in the embodiment and the comparative example is used as the negative electrode material of the lithium ion battery, mixed with a binder polyvinylidene fluoride (PVDF) and a conductive agent (Super-P) in a mass ratio of 91:7:2, and an appropriate amount of N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry, which is coated on a copper foil, and is vacuum dried and rolled to prepare a negative electrode sheet; a metal lithium sheet is used as a counter electrode, 1 mol / L LiPF6 and an electrolyte prepared by mixing a three-component mixed solvent in a ratio of EC:DMC:EMC=1:1:1 (v / v) are used, and a polypropylene microporous membrane is used as a diaphragm, and the cells are assembled into a CR2430 button cell in a glove box filled with an inert gas. The charge and discharge test of button battery was carried out on the Blue Electric Battery Test System of Guangdong Kaijin New Energy Technology Co., Ltd. At room temperature, 0.02C discharge for 300min, 0.05C discharge to 0.005V, stand for 10min, 0.05mA discharge to 0.005V, stand for 5min, 0.01mA discharge to 0.005V, 0.1C charge to 2V, the results are shown in Table 1.
[0071] Table 1 Test results
[0072]
[0073]
[0074] It can be seen from the results in Table 1 that, compared with Comparative Example 1-2, the graphite negative electrode material of Example 1-2 has better tap density, specific surface area and capacity performance. Specifically, the coating equipment in Comparative Example 1 adopts continuous kettle granulation for granulation, and the specific surface area, tap density, compaction density, gram capacity and oil absorption value of the negative electrode material after graphitization are all worse than those in Example 2. It may be that in this system, the horizontal kettle or the vertical kettle has more advantages; although Comparative Example 2 adopts a vertical kettle for granulation, the particle size span of the material after classification is large but there are many fine powders, that is, there are more particles with smaller particle sizes, and its specific surface area, tap density, compaction density, gram capacity and oil absorption value are not as good as those in Example 2. Example 2 selects a vertical kettle granulation equipment for the granulation process, and the particle size after classification is set to 4.5-5.0μm, with less fine powder and a small particle size span. After subsequent processes, the product particles can show that the secondary particles contain a small number of single particles, so that the particle size distribution is more reasonable, thereby improving the tap density, compaction density, reducing expansion, and improving the cycle performance.
[0075] Figure 2 The capacity retention rate curve of the battery made of the negative electrode materials of the embodiment and the comparative example after 500 cycles is shown. Figure 2 It can be seen that the cycle performances of Comparative Examples 1-2 are not as good as those of Examples 1-2, specifically, the cycle performance of Example 2 is the best, and the cycle performance of Comparative Example 1 is the worst.
[0076] In summary, the lithium-ion battery graphite negative electrode material prepared by the present invention has the characteristics of high capacity, high compaction, good compatibility with the electrolyte, excellent cycle performance, and good battery coating and processing performance.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a graphite negative electrode material for a lithium ion battery, characterized in that: Includes steps: (1) roughly crushing the raw materials to obtain material A; (2) crushing material A to obtain material C; (3) subjecting material C to classification treatment to obtain material D, wherein the DV50 of material D is 11-12 μm, and the DV10 is 4.0-4.5 μm or 4.5-5.0 μm; (4) Mixing material D and an adhesive to obtain material E; (5) Granulating material E to obtain material F, wherein the granulation equipment is a horizontal kettle or a vertical kettle; (6) Shaping material F to obtain material G; (7) Pre-carbonizing material G to obtain material H; (8) Graphitizing material H to obtain a graphitized material.
2. The method for preparing a lithium ion battery graphite negative electrode material according to claim 1, characterized in that: The raw material is selected from at least one of petroleum coke, coal-based coke, needle coke and semi-coke.
3. The method for preparing a lithium ion battery graphite negative electrode material according to claim 1, characterized in that: The DV50 of material C is 10-11 μm and the DV10 is 2.8-3.5 μm.
4. The method for preparing a lithium ion battery graphite negative electrode material according to claim 1, characterized in that: The adhesive is selected from at least one of high temperature asphalt, resin and liquid asphalt.
5. The method for preparing a lithium ion battery graphite negative electrode material according to claim 1, characterized in that: The equipment for mixed batch processing adopts one of the horizontal screw belt batch mixer or VC3000 batch mixer.
6. The method for preparing a lithium-ion battery graphite negative electrode material according to claim 5, characterized in that: The equipment for batch mixing is a horizontal screw mixer, and the temperature rise curve of the horizontal screw mixer is controlled from room temperature to 300°C within 1 hour, then to 650°C within 3 hours, and kept warm for 3 hours. The N2 flow rate is 0.5-1.0m 3 / h.
7. The method for preparing a lithium-ion battery graphite negative electrode material according to claim 1, characterized in that: The pre-carbonization temperature is 800-1200°C.
8. The method for preparing a lithium ion battery graphite negative electrode material according to claim 1, characterized in that: The pre-carbonization equipment is selected from a low-temperature carbonization furnace and a shuttle furnace.
9. The method for preparing a lithium-ion battery graphite negative electrode material according to claim 1, characterized in that: The graphitization temperature is 2900-3200℃.
10. The method for preparing a lithium-ion battery graphite negative electrode material according to claim 1, characterized in that: The graphitization equipment is selected from one of Acheson, box furnace and inner series furnace.
11. A graphite negative electrode material for a lithium-ion battery, characterized in that: The method is prepared by any one of claims 1 to 10.
Citation Information
Patent Citations
Artificial graphite negative electrode material used for lithium ion power batteries, and preparation method thereof
CN106058304A
Artificial graphite composite negative electrode material for lithium ion battery and preparation method for negative electrode material
CN107369823A